EXPERIMENTAL SCIENCE LEARNING AS AN INQUIRY-BASED PEDAGOGICAL FRAMEWORK FOR FOSTERING COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD EDUCATION - Ana Umimah; Pascalian Hadi Pradana; Rizki Sevi Triana (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study examines how experimental science learning fosters the cognitive development of children aged 5–6 years in early childhood education. Although previous studies have established the effectiveness of science experiments in improving science process skills and learning engagement, limited attention has been given to how inquiry experiences shape children's causal reasoning through contextual learning. This study addresses that gap by proposing experimental science learning as an integrated pedagogical framework linking contextual planning, inquiry-based implementation, and authentic assessment to children's cognitive development. The findings identify six interconnected inquiry stages that progressively support logical thinking and conceptual construction. This research employed a qualitative descriptive case study at KB Raudlatul Ulum, Jember City. The participants comprised 20 Group B children, while the school principal, one classroom teacher, and one assistant teacher served as key informants. Data were collected through participant observation, semi-structured interviews, documentation, and supporting questionnaires, then analyzed using an interactive qualitative approach involving data reduction, data display, and conclusion drawing. Credibility was strengthened through method and source triangulation. The findings indicate that contextual lesson planning, inquiry-oriented classroom interaction, and continuous authentic assessment collectively promoted children's observation, prediction, evidence verification, and reflective reasoning. Rather than merely introducing scientific concepts, experimental science learning facilitated the progressive construction of causal understanding, logical reasoning, and scientific habits of mind, highlighting inquiry as a comprehensive pedagogical process for strengthening early childhood cognitive development.